Energy prices and inflation expectations: Evidence from households and firms - Nils Wehrhöfer (Deutsche Bundesbank, 2023)
I investigate how households and firms adjust their inflation expectations when experiencing an increase in their energy prices. I use monthly panel survey data in combination with a difference-in-difference approach to show that households increase their inflation expectations when they personally experience an increase in their electricity prices. This result is inconsistent with full-information rational expectations but can be rationalized by households extrapolating their personal experience. The effect is driven by low-income households, households who are uninformed about past inflation, and those not trusting the ECB. Due to households extrapolating, their inflation forecasts become less accurate and diverge more from professional forecasts. Contrary to households, firms do not extrapolate energy price increases to their inflation expectations. Thus, decision-makers in firms form their expectations similarly to high-income households.
Keywords: D14; D22; D84; E31; Q41; 330; inflation expectations; households; firms; energy prices; extrapolation